Encapsulation technologies for active food ingredients and food processing - Nedovic, Viktor; Zuidam, Nicolaas Jan (Springer, 2009)
Edited by two leading experts, this is a valuable reference for those working on food processing using immobilized cells or enzymes, and on delivery of food compounds via encapsulation. The emphasis is on strategy, since encapsulation technologies may change